Health effects following subacute exposure to geogenic dust collected from active drainage surfaces (Nellis Dunes Recreation Area, Las Vegas, NV) - DeWitt, Jamie C.; Buck, Brenda J.; Goossens, Dirk; Teng, Yuanxin; Pollard, James; McLaurin, Brett T.; Gerads, Russell; Keil, Deborah E. (My University, 2017)
The specific health effects of direct inhalation of fine minerogenic dusts generated by natural soil surfaces remain poorly known and relatively little researched. To learn more about this exposure and its contri- bution to human health effects, we surveyed surface sediment and characterized dust from the Nellis Dunes Recreation Area (NDRA) in Clark County, Nevada, a popular off-road vehicle (ORV) recreational site. Dry drainage systems at NDRA are commonly used as natural trail systems for ORV recreation; these surfaces also are characterized by high concentrations of heavy metals. Geogenic dust with a median diameter of 4.05 􏰂m, collected from drainage surfaces at NDRA contained a total elemental concentra- tion of aluminum (79,651 􏰂g/g), vanadium (100 􏰂g/g), chromium (54 􏰂g/g), manganese (753 􏰂g/g), iron (33,266 􏰂g/g), cobalt (14 􏰂g/g), copper (37 􏰂g/g) zinc (135 􏰂g/g), arsenic (71 􏰂g/g), strontium (666 􏰂g/g), cesium (15 􏰂g/g), lead (34 􏰂g/g), and uranium (54.9 􏰂g/g). Adult female B6C3F1 mice exposed via oropha- ryngeal aspiration to 0.01–100mgdust/kg body weight, four times, a week apart, for 28-days, were evaluated for immuno- and neurotoxicological outcomes 24 h after the last exposure. Antigen-specific IgM responses were dose-responsively suppressed at 0.1, 1.0, 10 and 100 mg/kg. Splenic lymphocytic subpopulations, hematological and clinical chemistry parameters were affected. In brain tissue, antibod- ies against NF-68, and GFAP were not affected, whereas IgM antibodies against MBP were reduced by 26.6% only in the highest dose group. A lowest observed adverse effect level (LOAEL) of 0.1 mg/kg/day and a no observed adverse effect level (NOAEL) of 0.01 mg/kg/day were derived based on the antigen primary IgM responses after subacute exposure to this geogenic dust.